IgG subclasses as biomarkers for persistence of factor VIII inhibitors in previously untreated patients with severe haemophilia A. (14th December 2020) - Peyvandi, Flora; Miri, Syna; Bucciarelli, Paolo; Valsecchi, Carla; Schiavone, Lucia; Boscarino, Marco; Palla, Roberta; Mannucci, Pier Mannuccio; Rosendaal, Frits Richard; ,
Summary: We investigated longitudinally the behaviour of anti‐factor VIII (anti‐FVIII) IgG subclasses for 6 months from inhibitor development in 43 patients from the Survey of Inhibitors in Plasma‐Products Exposed Toddlers (SIPPET) trial who developed persistent or transient inhibitors. We first analysed 43 patients within 60 days post inhibitor detection. Then, 14 of these 43 patients were studied at five time points over 6 months. Our study showed that during the first 60 days, the risk of inhibitor persistence increased with the concomitant presence of an increasing number of IgG subclasses. Over the 6‐month period post inhibitor detection, only the IgG2 subclass could be considered a hallmark of inhibitor persistence.